A constituição enunciativa do mundo social - Alice Horikawa Yoko; Maria Cecília Magalhães Camargo (EccoS – Revista Científica)
The notion of representation has been receiving noteworthy distinction in the new analysis of the social relationship which associates the human beings social constitution with his or her own ways of language. The aim of this paper is both to show some of the discussions that have been hold about concept, mainly in which it refers to its relation to the verbal language, and to present Bakhtins Enunciation Theory as being a possibility of avoiding the risk of nihilism that involves some of these approaches.